Morphological characterization of swiftlet species (collocalia sp.): beak, nest and saliva - Aziz, Norazlin Abdul (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2005)
Swiftlets are special kind of swift which is known to be the commercial edible bird's nest builder. This rare delicacy, which is famously known as the 'Caviar of the East' has very high value in the market were made up of glutinous strand of muciginous saliva secretion of the swiftlets. Seeing that not much effort has been done to characterize or properly identify the anatomical and morphological features of the bird's nest and the swiftlet, this pilot research was conducted as preliminary work towards developing this field of research into further studies. This research conducted utilized a very high tech probe, VPSEM incorporated with EDX to yield a morphological topography as well as trace element analysis of the subject concerned in the study. Before this approach was taken, we concluded to believe that the vast salivary secretions of the swiftlets actually come from the paired sublingual gland. However, results of the study showed that there are many other interesting and predominant features that may alter this fact as well as providing an insight towards understanding the nesting behaviour of the species. As a conclusion, these features found during the pilot research were bound to be suggestive of certain characteristic of the swiftlets species that may have not been discovered by any researcher before.